Understanding the Pesticide Label for Citrus Grove Workers - Brian Boman; Darren Cole; Steve Futch; Ward Gunter; Jack Hebb; P. Chris Wilson (EDIS, 2007)
ABE-367, a 6-page illustrated fact sheet by Brian Boman, Darren Cole, Steve Futch, Ward Gunter, Jack Hebb, and Chris Wilson, instructs citrus grove workers in reading pesticide labels. Includes a quiz and references. Published by the UF Department of Agricultural and Biological Engineering, August 2007.